2016
DOI: 10.1038/srep33132
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of calcium/calmodulin-stimulated protein kinase II at T286 enhances invasion and migration of human breast cancer cells

Abstract: Calcium/calmodulin-stimulated protein kinase II (CaMKII) is a multi-functional kinase that controls a range of cellular functions, including proliferation, differentiation and apoptosis. The biological properties of CaMKII are regulated by multi-site phosphorylation. However, the role that CaMKII phosphorylation plays in cancer cell metastasis has not been examined. We demonstrate herein that CaMKII expression and phosphorylation at T286 is increased in breast cancer when compared to normal breast tissue, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…Moreover, enhanced expression of CaMK-II in human breast cancer cells, as compared to normal breast tissue, and its activation by CaM leading to autophosphorylation at T286 positively correlated with increased invasiveness, anchorage-independent growth and lower metastasis-free survival rate. Furthermore, transfection with the phospho-mimetic T286D CaMK-II mutant plasmid, rendering this enzyme in a constitutive active form, resulted in FAK phosphorylation, which further enhanced the migratory and invasive capacity of the tumor cells, suggesting that CaMK-II plays a key role in metastasis [230]. The authors of this report proposed that targeting CaMK-II could be a good choice to inhibit breast cancer metastasis.…”
Section: Cam-dependent Protein Kinasesmentioning
confidence: 88%
“…Moreover, enhanced expression of CaMK-II in human breast cancer cells, as compared to normal breast tissue, and its activation by CaM leading to autophosphorylation at T286 positively correlated with increased invasiveness, anchorage-independent growth and lower metastasis-free survival rate. Furthermore, transfection with the phospho-mimetic T286D CaMK-II mutant plasmid, rendering this enzyme in a constitutive active form, resulted in FAK phosphorylation, which further enhanced the migratory and invasive capacity of the tumor cells, suggesting that CaMK-II plays a key role in metastasis [230]. The authors of this report proposed that targeting CaMK-II could be a good choice to inhibit breast cancer metastasis.…”
Section: Cam-dependent Protein Kinasesmentioning
confidence: 88%
“…Our study also offered a possibility to explore the transcriptional regulatory functions of MGP for other transcription factors. Moreover, several previous studies demonstrated cross‐linking regulatory effects of calcium signal on STAT5 pathway (Chi et al , 2016); however, the mechanism is not clear. MGP is known to have a strong calcium‐binding capacity, which suggests MGP may regulate STAT5 transcriptional activity by mediating calcium binding to MGP‐STAT5 complex at the promoter regions of downstream target genes.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, CaMK2B, but not CaMK2A neither CaMK2D, appeared as a valuable indicator of stroke patient functional outcome. CaMK2B association to disease prognosis has been previously reported in cancer 62 but, as far as we know no previous study has explored CaMK2B prognosis-value by measuring its levels in the circulation. Thus, in this preliminary study we are newly describing that circulating levels of CaMK2B showed a potential to predict stroke patients outcome, though larger studies are required to corroborate these findings and to assess whether this predictive capacity is unique to CaMK2B, which is the most brain-specific protein of the CaMK2 members 35 , and whether it turns out to also be a potential target to therapeutically modulate the progression of the ischemic lesion.…”
Section: Discussionmentioning
confidence: 99%